Body image and health-related behaviors among fitspirit participants - Manon Bordeleau; Jo-Anne Gilbert; Natalie Alméras; Johana Monthuy-Blanc; Joël Gagnon; Marie-Ève Mathieu; Vicky Drapeau (BMC, 2022)
Abstract Background Body image variables such as body size perception (BSP) and body size dissatisfaction (BSD) can influence health-related behaviors. However, few studies have investigated these body image variables in adolescent girls participating in a physical activity intervention. Therefore, the study objectives were to examine the 1) associations between health-related behaviors (physical activity, screen-time, eating habits and sleep duration) and BSP and BSD among girls participating in FitSpirit, a physical activity intervention for girls; and 2) influence of weight control practices on the association between health-related behaviors and BSP and BSD. Methods This cross-sectional study assessed a sample of 545 adolescent girls (mean age: 15.0±1.5 years) from 240 schools. Body mass index, health-related behaviors, perceived actual body size and desired body size variables were self-reported and collected via an online questionnaire at the end of the FitSpirit intervention. A negative BSP score [perceived actual body size - calculated BMI z-score] indicates an underestimation of body size. A positive BSD score [perceived actual body size - desired body size] indicates a desire to reduce body size. A multiple linear regression analysis examined the effects of age, zBMI and health behaviors on BSP and BSD. A second multiple linear regression analysis examined the independent associations between BSP and BSD by weight control practice. The linear relationships between BSP and BSD were evaluated with Pearson's correlations. Results Underestimation and dissatisfaction of body size are more prevalent in participants living with overweight/obesity. Screen-time and sleep duration were independently associated with BSP score (Beta=0.02; P<0.05 and Beta=-0.07; P<0.05, respectively), whereas only screen-time was associated with the BSD score (Beta=0.07; P<0.001). Physical activity was independently associated with the BSP score only in participants trying to control (maintain) their weight (Beta=-0.18; P<0.05). Conclusions Body size overestimation and dissatisfaction are associated with health-related behaviors, specifically with more screen-time and less optimal sleeping habits. Physical activity level does not appear to be associated with body image in girls engaged in a physical activity intervention and who want to lose or gain weight. Health promotion interventions could include screen-time and sleep components as they may influence body image.